Mejora de la Tecnología de desverdización de cítricos y aptitud a la frigoconservación de nuevas variedades. Estudios sobre parámetros de calidad y composición nutricional - Sdiri, Sawsen (2021)
Citrus fruits are attractive fruits sought after by consumers overall the world for their unique taste, flavor, eating quality and health benefits. After harvest, fresh citrus fruit need to be manipulated at different stages with postharvest treatments before reaching consumers. Degreening process, by exposing fruit to ethylene, is a postharvest treatment, commonly used to accelerate external color change of citrus fruit since in the Mediterranean area early-season citrus fruit are harvested when fruit reach acceptable internal maturity standards for marketing while their external peel color is still green. Nevertheless, the application of ethylene during degreening treatment, besides the desirable color change, can induce physiological disorders related to peel and calyx senescence (browning and dropping). One objective of the present Thesis was to study different postharvest treatments to improve quality of early-season citrus fruit submitted to degreening treatment. The application of degreening treatments combining periods without ethylene exposure with other with ethylene application significantly reduced the calyx alterations associated with this treatment without affecting the external color evolution. The postharvest application of HFCalibra®, a growth regulator, also decreased the calyx alteration incidence in all assayed varieties; the higher the doses applied, the lower percentage of fruit with calyx alterations symptom.